Hypertension Subtypes among Thai Hypertensives: An Analysis of Telehealth-Assisted Instrument in Home Blood Pressure Monitoring Nationwide Pilot Project. (9th April 2020) - Montrivade, Sakolwat; Chattranukulchai, Pairoj; Siwamogsatham, Sarawut; Vorasettakarnkij, Yongkasem; Naeowong, Witthawat; Boonchayaanant, Patchaya; Sakulsupsiri, Anut; Ariyachaipanich, Aekarach; Lertsuwunseri, Vorarit; Rungpradubvong, Voravut; Satitthummanid, Sudarat; Puwanant, Sarinya; et al.
Abstract : Background . White-coat hypertension (HT), masked HT, HT with white-coat effect, and masked uncontrolled HT are well-recognized problems of over- and undertreatment of high blood pressure in real-life practice. However, little is known about the true prevalence in Thailand. Objectives . To examine the prevalence and characteristics of each HT subtype defined by mean home blood pressure (HBP) and clinic blood pressure (CBP) using telemonitoring technology in Thai hypertensives. Methods . A multicenter, observational study included adult hypertensives who had been diagnosed for at least 3 months based on CBP without the adoption of HBP monitoring. All patients were instructed to manually measure their HBP twice a day for the duration of at least one week using the same validated automated, oscillometric telemonitoring devices (Uright model TD-3128, TaiDoc Corporation, Taiwan). The HBP, CBP, and baseline demographic data were recorded on the web-based system. HT subtypes were classified according to the treatment status, CBP (≥or <140/90 mmHg), and mean HBP (≥or <135/85 mmHg) into the following eight subtypes: in nonmedicated hypertensives, there are four subtypes that are normotension, white-coat HT, masked HT, and sustained HT; in treated hypertensives, there are four subtypes that are well-controlled HT, HT with white-coat effect, masked uncontrolled HT, and sustained HT. Results . Of the 1, 184 patients (mean age 58 ± 12.7 years, 59% women) from 46 hospitals, 1, 040 (87.8%) were taking antihypertensive agents. The majority of them were enrolled from primary care hospitals (81%). In the nonmedicated group, the prevalence of white-coat and masked HT was 25.7% and 7.0%, respectively. Among the treated patients, the HT with white-coat effect was found in 23.3% while 46.7% had uncontrolled HBP (a combination of the masked uncontrolled HT (9.6%) and sustained HT (37.1%)). In the medicated older subgroup ( n = 487), uncontrolled HBP was more prevalent in male than in female (53.6% vs. 42.4%, p = 0.013 ). Conclusions . This is the first nationwide study in Thailand to examine the prevalence of HT subtypes. Almost one-fourth had white-coat HT or HT with white-coat effect. Approximately half of the treated patients especially in the older males had uncontrolled HBP requiring more intensive interventions. These results emphasize the role of HBP monitoring for appropriate HT diagnosis and management. The cost-effectiveness of utilizing THAI HBPM in routine practice needs to be examined in the future study.